Building Open Education Capacity: Introducing the Canadian Code of Best Practices in Fair Dealing for Open Educational Resources - Joshua Dickison; Rowena Johnson; Ann Ludbrook; Heather Martin; Stephanie Savage (Journal of Copyright in Education and Librarianship)
This article builds upon a presentation given at the 2024 ABC Copyright Conference in which the authors outlined the process for adapting the Code of Best Practices in Fair Use for Open Educational Resources (OER) for a Canadian audience. Originally published in 2021, the U.S. Code is an important tool for evaluating common OER use cases, providing a framework of analysis that can guide a creator towards making judiciously defensible fair use decisions. Alongside practical guidance, the Code represents a significant contribution in support of the United Nations Educational, Scientific and Cultural Organization (UNESCO)’s Recommendation on OER, which encourages member states to build capacity concerning exceptions and limitations for the use of copyrighted works for educational and research purposes. Supported by the Canadian Association of Research Libraries, the Canadian Adaptation Working Group began their adaptation process in late 2021 and the final Code was published in early 2024. In addition to providing an overview of the adaptation process, this article offers a comprehensive summary of the legal considerations that informed the writing of the Code and provides examples of how the Code has been operationalized at educational institutions in Canada.